Sensitivity of ultrasound scan and hysteroscopy with histopathological correlation in identifying endometrial pathology for a mixed group of symptomatic and asymptomatic patients - Shetty, Ashwin; Dalal, Asha; Manwani, Saloni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: We wished to correlate abnormal findings on hysteroscopy with abnormal findings on Ultrasound. To study the accuracy of ultrasound for detection of uterine polyps using hysteroscopy as gold standard. Analyse the cases detected with Carcinoma Endometrium and other endometrial pathology. Methods: In this retrospective study, we summarized data from 125 patients who underwent TVS examination followed by hysteroscopy under 2 consultants from 2017 to 2020. Specimens were obtained and sent for histopathological examination. Sensitivity, specificity, positive and negative predictive values for diagnosing uterine pathology were calculated for each method. Results: The sensitivity and specificity of ultrasonography for identifying polyps is 27.03% and 98.04% respectively The sensitivity of ultrasonography for identifying any abnormal pathology is 90.08%. A total of 74 hysteroscopy identified and histology confirmed polyps were identified with no incidence of cancer in all the polyps. A total of 8 patients were diagnosed to have Endometrial Cancer on endometrial biopsy. Of these 8, 7 were postmenopausal and 1 premenopausal. 2 patients of these were asymptomatic with incidental finding of thickened endometrium on ultrasonography. Conclusions: Transvaginal ultrasound is a practical approach for initial evaluation of abnormal uterine bleeding, however a hysteroscopy would be necessary in most of the suspicious cases due to better diagnostic accuracy. A unique feature of this study is the inclusion of a group of asymptomatic women incidentally detected to have uterine pathology including uterine carcinoma on routine health examination hence highlighting the importance of routine gynaecological check especially in the peri and post-menopausal age group.